THE CORRELATION BETWEEN READING HABIT AND NARATIVE TEXT WRITING ABILITY OF TENTH-GRADE STUDENTS OF SMA N 1 RENDANG IN ACADEMIC YEAR 2020/2021 - Ni Komang Sariningsih; Ni Luh Putu Dian Sawitri; Luh Ketut Sri Widhiasih (Academic Journal on English Studies (AJOES), 2021)
The aim of this study was to define the relationship between students' reading habits and their narrative writing abilities. The population of this study were students of class X SMA 1 Rendang. A product moment correlation method is applied in this study. There are two instruments for collecting data; namely the instrument to measure students' reading habits, in this case was a questionnaire, and the instrument to measure students' ability to write narrative, which is a text construction test. The result shows that there is a significant relationship between students' reading habits and the ability to write narrative text in class X SMA 1 Rendang. Therefore, it can be concluded that the more students read, the better their narrative writing skills.